Application of Common Greenbottle Fly (Lucilia sericata Meigen, 1826) Larvae Extract for Incision Wound Treatments in Rats - Madihah Madihah; Lisda Mawarni Sihotang; Desak Made Malin; Wawan Hermawan (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Common green-bottle fly (Lucilia sericata) larvae have been used in maggot debridement therapy to promote wound healing since the 19th century following the emergence of an antibiotic-resistant strain of bacteria. Whole body extracts and hemolymph of L. sericatalarvae shown antibacterial properties. This research aims to examine the ethanol extract from whole body of L. sericatalarvae to accelerate the wound healing on the skin of male Wistar rats (Rattus norvegicus). The method was a completely randomized design with six treatments and four replications each. The incision wound created at the dorsolateral region of shaven skin at ±1.5 cm using sterile scissors. The extract at concentration 5, 10 and 20% in olive oil were applied topically to wounded rats, as well as Betadine® for the reference group. For positive control only olive oil applied to wounded rats, as for negative control was non-treated wounded rats. The treatment was done twice a day for 14 days. At day 15th, the wounded site harvested, fixed in 10% NBF, embedded in paraffin, and sectioned at 5-7 µm, then stained with hematoxylin-eosin or trichrome Heidenhain’s Azan for histological examination. The results showed that topical application of the L. sericata larvae extract at concentration 10% was significantly recover the wounded skin by enhanced re-epithelialization, narrowed granulation tissue, as well as increased capillary number and collagen density than other treatments (p<0.05). Overall, our data support the L. sericatalarva extract as an agent to accelerate the wound healing process on skin.Key words: ethanol extract, green-bottle fly, incision wound, whole body larva, wound healing.